Bipolar disorder and the gut microbiome: A systematic review. (1st March 2021) - Sublette, M. Elizabeth; Cheung, Stephanie; Lieberman, Evan; Hu, Shaohua; Mann, J. John; Uhlemann, Anne‐Catrin; Miller, Jeffrey M.
Abstract: Objectives: The microbiome is a rapidly advancing biomedical frontier with relevance for psychiatric illness. The gut microbiota interact with the central nervous system bidirectionally through the gut–brain axis and generate substances that may influence host metabolism, including short‐chain fatty acids such as butyrate. Understanding gut microbiota in bipolar disorder (BD) may suggest new disease markers and treatment approaches. Methods: A PubMed search was performed on January 7, 2020 using terms "bipolar AND (microbiome OR microbiota)", for articles in English in which the study population included a distinct BD group and the gut microbiota/microbiome was assessed. Results: Thirteen articles met the inclusion criteria. In four of five studies that reported on group comparisons with respect to diversity, lower α‐diversity was observed in BD relative to healthy controls (HC). The most convergent taxonomic finding was that in four studies, one particular clade distinguished gut microbiota between BD and HC: family Ruminococcaceae, genus Faecalibacterium, and species Faecalibacterium prausnitzii . Members of this clade, known for butyrate production, were reduced in BD relative to HC in three studies but elevated in a fourth. Additionally, genera Bacteroides or Bacteroides–Prevotella group species were elevated in BD in two studies but lower in a third. Conclusions: Despite few studies and modest sample sizes, salient findings suggest that low α‐diversity and dysbiosis with respect to abundance of Faecalibacterium and Bacteroides may characterize BD in both a trait and state‐dependent fashion. Decreased richness and butyrate production also foster inflammation, which may be a hitherto unrecognized part of the pathophysiology underlying BD.